How do you evaluate -9+ \frac { 3} { 2} ( - 4a - 6)?

1 Answer
Sep 16, 2017

-6a-18

Explanation:

First, we will focus on 3/2(-4a-6).

We will use this: x*y/z=(x*y)/z

So it would be: (-4a-6)*3/2=(3(-4a-6))/2.

Now I will focus on the numerator which is 3(-4a-6).
We will focus on (-4a-6). We will factor out the number 2.

-4a-6=2(2a+3). Now, put in the 3 back so the equation would be:

-2color(blue)*color(blue)3(2a+3) which is -6(2a+3). Now put in the fraction back.

The equation would be: -(6(2a+3))/2.
Divide the numbers 6/2=3.

Equation: -3(2a+3)

Now we will use: x(y+z)=xy+xz to distribute the brackets/parentheses. Imagine that x=-3, y=2a and z=3.

Using x(y+z)=xy+xz, the equation will be -3(2a+3)=-3*2+ -3*3 which is the same as -3*2a-3*3.

Next, we multiply the numbers 3*2=6.
The equation would be -6a-3*3.
Multiply the numbers 3*3=9. to make it -6a-9. Add in the -9 that you have to make the whole equation -9-6a-9.

Now we will simplify -9-6a-9. We will group like terms to -6a-9-9. Subtract the numbers -9-9=-18.

The final equation would be -6a-18.